Lithium ferrite lithium supplement agent and preparation method and application thereof
By using low-temperature molten salt method and rapid annealing method to coat the solid electrolyte LATP on the surface of Li5FeO4, the shortcomings of Li5FeO4 lithium supplementation agent in air stability and lithium supplement efficiency are solved, forming a composite lithium supplementation agent, and improving its use in lithium-ion batteries electrochemical properties and cyclic stability in the
Patent Information
- Application Number
- CN202510035211.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2045-01-09
AI Technical Summary
Li5FeO4, as a lithium supplement agent, has shortcomings in air stability and lithium supplement efficiency, and its structural stability, interface reaction and electron ion conductivity are insufficient, which affects its application in lithium-ion batteries.
The solid electrolyte LATP is coated on the surface of Li5FeO4 by low-temperature molten salt method and rapid annealing method to form a composite lithium supplement agent to improve its air stability and lithium supplement efficiency.
The air stability and lithium replenishment efficiency of Li5FeO4 are improved through the solid electrolyte coating, forming a composite lithium replenishment agent, enhancing its electrochemical performance and cycling stability in lithium-ion batteries.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to a lithium ferrite lithium supplement, a preparation method and application thereof. Background Art
[0002] In modern energy storage technology, lithium-ion batteries have become the dominant force due to their high energy density, long cycle life and relatively mature technical foundation. In order to meet the growing demand for high energy density, researchers have been exploring cathode materials with higher theoretical specific capacity. Li5FeO4, as an olivine-structured cathode material, has attracted much attention due to its high specific capacity and low-cost iron source.
[0003] However, there are some challenges in the practical application of Li5FeO4 materials, mainly including:
[0004] Air stability: Li5FeO4 easily reacts with moisture and carbon dioxide in the air, causing the material to de-lithiate and generate LiFeO2, which affects its performance as a lithium supplement;
[0005] Structural stability: Li5FeO4 may undergo structural changes during the charge and discharge process, including phase change and volume expansion, which may lead to a decrease in the mechanical strength of the material and thus affect the cycle stability of the battery;
[0006] Interface reaction problem: Side reactions with the electrolyte may lead to the formation of an unstable SEI layer, increasing the irreversible capacity loss of the battery;
[0007] Insufficient electronic and ionic conductivity: Low electronic and ionic conductivity limits the charge and discharge performance of Li5FeO4, especially under high rate conditions.
[0008] To solve these problems, surface coating technology has been widely studied. As a solid electrolyte material, LATP has good lithium ion conductivity and chemical stability, making it an ideal choice for coating modification. However, traditional LATP coating methods often require high-temperature treatment, which may cause structural damage to the Li5FeO4 material and uneven coating layer. Summary of the invention
[0009] In view of this, the technical problem to be solved by the present invention is to provide a lithium ferrite lithium supplement agent, a preparation method and application thereof. The preparation method utilizes a low-temperature molten salt method and a rapid annealing method to coat LATP on the surface of Li5FeO4 to solve the deficiencies of Li5FeO4 as a lithium supplement agent in the prior art in terms of air stability and lithium supplement efficiency.
[0010] The present invention provides a method for preparing a lithium ferrite lithium supplement, comprising the following steps:
[0011] S1) mixing an organic carbon source with iron oxide, and performing a first calcination in a protective atmosphere to obtain a carbon-supported iron oxide material;
[0012] S2) mixing the carbon-supported iron oxide material with a lithium source, and performing a second calcination in a protective atmosphere to obtain a carbon-doped lithium iron oxide material;
[0013] S3) The mixed lithium salt and the raw material of the surface coating layer except the lithium element are mixed for the first time, and then the carbon-doped lithium iron oxide material is added for a second mixing, and then calcined for a third time in an oxygen-containing atmosphere and cooled to obtain a lithium ferrite lithium supplement; the mixed lithium salt includes a first lithium salt, a second lithium salt and a third lithium salt; the melting point of the first lithium salt is greater than the melting point of the second lithium salt and the difference is greater than 100°C; the melting point of the third lithium salt is greater than the melting point of the first lithium salt and the difference is greater than 100°C; the surface coating layer is a solid electrolyte.
[0014] Preferably, the mass ratio of the first lithium salt, the second lithium salt and the third lithium salt is (80-95):(3-15):(2-5).
[0015] Preferably, the organic carbon source is selected from one or more of glucose, polydopamine, resorcinol-formaldehyde resin, polyvinyl pyrrolidone, tannic acid, citric acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene, and aniline;
[0016] The lithium source is selected from one or more of lithium oxide, lithium hydroxide, lithium oxalate and lithium carbonate;
[0017] The first lithium salt is selected from lithium carbonate and / or lithium hydroxide;
[0018] The second lithium salt is selected from one or more of lithium nitrate, lithium squarate, lithium acetate and lithium oxalate;
[0019] The third lithium salt is selected from lithium fluoride and / or lithium chloride.
[0020] Preferably, the mass ratio of the organic carbon source to iron oxide is (0.01-0.05): (1-5);
[0021] The molar ratio of iron oxide to lithium source in the carbon-supported iron oxide material is 1:(5-7).
[0022] Preferably, the mixing in step S1) is carried out in an organic solvent, and after drying, the first calcination is carried out in a protective atmosphere; the ratio of iron oxide to organic solvent is (1-5) kg: (3-5) L; the mixing speed is 100-500 rpm; the mixing time is 3-12 h;
[0023] The mixing in step S2) is performed by grinding;
[0024] In the step S3), the rotation speed of the first mixing is 500-1000 rpm; the time of the first mixing is 1-10 min; the rotation speed of the second mixing is 2000-3000 rpm; the time of the second mixing is 20-60 min.
[0025] Preferably, the temperature of the first calcination is 300°C to 500°C; the time of the first calcination is 3 to 6 hours; the heating rate of the first calcination is 1 to 10°C / min;
[0026] The temperature of the second calcination is 650°C to 850°C; the time of the second calcination is 12 to 30 h; the heating rate of the second calcination is 1 to 10°C / min;
[0027] The temperature of the third calcination is 500° C. to 700° C.; the time of the third calcination is 6 to 15 h; and the heating rate of the third calcination is 1 to 10° C. / min.
[0028] Preferably, the cooling rate in step S3) is 20-40°C / min.
[0029] Preferably, the surface coating layer is lithium titanium aluminum phosphate solid electrolyte or lithium lanthanum zirconium oxygen solid electrolyte;
[0030] The mass ratio of the total mass of the mixed lithium salt and the raw materials of the surface coating layer except the lithium element to the carbon-doped lithium iron oxide material is (1-10): (8-12).
[0031] The present invention also provides a lithium ferrite lithium supplement prepared by the above preparation method.
[0032] The present invention also provides a lithium ion battery, comprising the lithium ferrite lithium supplement prepared by the above preparation method.
[0033] Compared with the prior art, the present invention has the following beneficial effects:
[0034] 1) Improving air stability: The present invention forms a solid electrolyte coating layer on the surface of the carbon-doped lithium iron oxide material through a low-temperature molten salt method, which can effectively isolate the air, improve the air stability of the material, reduce the delithiation phenomenon, and maintain the structural integrity and lithium replenishment performance of the material;
[0035] 2) Optimizing lithium replenishment efficiency: When Li5FeO4 is used as a lithium replenisher, its lithium replenishment efficiency is limited by the electronic conductivity and ion diffusion of the material itself. The low-temperature molten salt method used in the present invention can achieve uniform coating of solid electrolyte at a lower temperature, which helps to improve the electronic conductivity and ion diffusion of carbon-doped lithium iron oxide materials, thereby optimizing the lithium replenishment efficiency;
[0036] 3) Formation of a composite lithium supplement: The present invention proposes to use a low-temperature molten salt method to coat a solid electrolyte on the surface of a carbon-doped lithium iron oxide material to form a new type of composite lithium supplement. This composite lithium supplement combines the high theoretical lithium supplement capacity of Li5FeO4 and the excellent ionic conductivity of the solid electrolyte, and can improve the electrochemical performance of the material while maintaining a high lithium supplement capacity;
[0037] 4) Broadening the application scenarios: Through solid electrolyte coating modification, the composite lithium supplement of the present invention has potential applications not only in high energy density lithium-ion batteries, but also in a wider range of application scenarios, such as under extreme temperature conditions or in applications requiring higher safety;
[0038] 5) Reducing the delithiation energy barrier: The introduction of the solid electrolyte coating can reduce the delithiation energy barrier of Li5FeO4, making it easier to release lithium ions during the electrochemical process, thereby more effectively compensating for the active lithium consumed by the formation of the negative electrode SEI during the first charge process;
[0039] 6) Improving the overall performance of the battery: By improving the air stability and lithium replenishment efficiency of the lithium replenisher, the composite lithium replenisher of the present invention helps to improve the initial coulombic efficiency and cycle stability of the battery, thereby improving the overall performance of the battery.
[0040] In summary, the low-temperature molten salt solid electrolyte of the present invention is coated with Li5FeO4 to form a composite lithium supplement, which provides a new technical solution for the commercial application of high energy density lithium-ion batteries by improving air stability and lithium supplement efficiency. DETAILED DESCRIPTION
[0041] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The invention provides a preparation method of a lithium ferrite lithium supplement, comprising the following steps: S1) mixing an organic carbon source with iron oxide, and performing a first calcination in a protective atmosphere to obtain a carbon-loaded iron oxide material; S2) mixing the carbon-loaded iron oxide material with a lithium source, and performing a second calcination in a protective atmosphere to obtain a carbon-doped lithium iron oxide material; S3) mixing a mixed lithium salt with a raw material except lithium element of a surface coating layer for a first time, then adding the carbon-doped lithium iron oxide material for a second mixing, performing a third calcination in an oxygen-containing atmosphere, and cooling to obtain a lithium ferrite lithium supplement; the mixed lithium salt comprises a first lithium salt, a second lithium salt and a third lithium salt; the melting point of the first lithium salt is greater than the melting point of the second lithium salt and the difference is greater than 100°C; the melting point of the third lithium salt is greater than the melting point of the first lithium salt and the difference is greater than 100°C; the surface coating layer is a solid electrolyte.
[0043] The carbon coated on the surface of lithium-rich lithium ferrite is used to increase the surface temperature of the lithium-rich lithium ferrite material. At the same time, a composite lithium salt is used to form a molten salt to increase the internal reaction temperature and increase the fluidity of the lithium salt. A solid electrolyte coating layer is synthesized at low temperature. Finally, rapid annealing is used to cool down and construct internal defects, so that the solid electrolyte coated on the surface forms a lithium ion channel, expands the lithium ion transmission rate, and increases ion conductivity.
[0044] After conventional lithium-rich lithium ferrite is supplemented with lithium, an inert substance, lithium ferrite, is formed. However, the present invention uses a solid electrolyte to coat the lithium-rich lithium ferrite. After lithium supplementation, the solid electrolyte can provide a fast ion channel, mitigate the impact of the inert substance, and reduce the internal resistance.
[0045] The present invention has no particular limitation on the sources of all raw materials, and any raw materials available on the market can be used.
[0046] An organic carbon source is mixed with iron oxide; the organic carbon source can be an organic carbon source well known to those skilled in the art without any special restrictions, and in the present invention, it is preferably one or more of glucose, polydopamine, resorcinol-formaldehyde resin, polyvinyl pyrrolidone, tannic acid, citric acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene and aniline; the mass ratio of the organic carbon source to the iron oxide is preferably (0.01-0.05): (1-5), more preferably (0.01-0.03): (1-3), more preferably 0.01: (1-2), and most preferably 0.01: 1; the mixing method can be a method well known to those skilled in the art without any special restrictions, and in the present invention, it is preferably liquid phase mixing, specifically carried out in an organic solvent, and then dried; the organic solvent can be an organic solvent well known to those skilled in the art without any special restrictions, and in the present invention, it is preferably an alcohol solvent, more preferably ethanol; the ratio of the iron oxide to the organic solvent is preferably (1-5) kg: (3-5) L; in some embodiments provided by the present invention, the ratio of the iron oxide to the organic solvent is specifically 1 kg: 3 L or 1 kg: 1 L; the mixing speed is preferably 100-500 rpm, more preferably 200-500 rpm; the mixing time is preferably 3-12 h; the drying temperature is preferably 50°C-100°C; the drying time is preferably 12-24 h.
[0047] After drying, preferably after grinding, the first calcination is carried out in a protective atmosphere to obtain a carbon-loaded iron oxide material; the protective atmosphere can be a protective atmosphere well known to those skilled in the art, and there is no special limitation. In the present invention, nitrogen is preferably used; the temperature of the first calcination is preferably 300°C to 500°C; the time of the first calcination (i.e., the insulation time) is preferably 3 to 6 h; the heating rate of the first calcination is preferably 1 to 10°C / min, more preferably 2 to 8°C / min, more preferably 4 to 6°C / min, and most preferably 5°C / min.
[0048] The carbon-supported iron oxide material is mixed with a lithium source, and a second calcination is performed in a protective atmosphere to obtain a carbon-doped lithium iron oxide material; the lithium source can be a lithium source well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably one or more of lithium oxide, lithium hydroxide, lithium oxalate and lithium carbonate; the molar ratio of iron oxide to lithium source in the carbon-supported iron oxide material is preferably 1:5~1:7, and more preferably 1:5~1:6; the mixing is performed by grinding; the protective atmosphere can be a protective atmosphere well known to those skilled in the art, and there is no special restriction. In the present invention, it is preferably nitrogen; the temperature of the second calcination is preferably 650°C~850°C; the time of the second calcination (i.e., the insulation time) is preferably 12~30 h, and more preferably 12~24 h; the heating rate of the second calcination is 1~10°C / min, more preferably 2~8°C / min, more preferably 4~6°C / min, and most preferably 5°C / min.
[0049] The mixed lithium salt is mixed for the first time with the raw material of the surface coating layer except the lithium element; the mixed lithium salt includes a first lithium salt, a second lithium salt and a third lithium salt; the melting point of the first lithium salt is greater than the melting point of the second lithium salt and the difference is greater than 100°C, preferably greater than 120°C; the melting point of the third lithium salt is greater than the melting point of the first lithium salt and the difference is greater than 100°C, preferably greater than 120°C; more specifically, the first lithium salt is preferably lithium carbonate and / or lithium hydroxide; the second lithium salt is preferably one or more of lithium nitrate, lithium squarate, lithium acetate and lithium oxalate; the third lithium salt is preferably lithium fluoride and / or lithium chloride; the mass ratio of the first lithium salt, the second lithium salt and the third lithium salt is preferably (80-95): (3-15): (2-5); in some embodiments provided by the present invention, the mass ratio of the first lithium salt, the second lithium salt and the third lithium salt is specifically 80:15:5 or 95:3:2; the surface coating layer is a solid electrolyte, preferably a lithium titanium aluminum phosphate solid electrolyte or a lithium lanthanum zirconium oxide solid electrolyte; when the surface coating layer is a lithium titanium aluminum phosphate solid electrolyte, the raw materials except the lithium salt preferably include an aluminum source, a titanium source and a phosphorus source; the aluminum source can be an aluminum source well known to those skilled in the art, and there is no The present invention is preferably aluminum oxide; the titanium source can be a titanium source well known to those skilled in the art, without any special restrictions, and is preferably titanium oxide in the present invention; the phosphorus source can be a phosphorus source well known to those skilled in the art, without any special restrictions, and is preferably ammonium dihydrogen phosphate and / or diammonium hydrogen phosphate in the present invention; the molar ratio of the mixed lithium salt, aluminum source, titanium source and ammonium dihydrogen phosphate is preferably x:y:z:3; the x+z=3, y=x-1, y is 0.1~0.5, more preferably 0.2~0.4, and more preferably 0.3~0.4; when the surface coating is lithium lanthanum zirconium oxide Solid electrolyte, the raw materials except lithium salt preferably include zirconium source and lanthanum source; the zirconium source can be a zirconium source well known to those skilled in the art, without any special restrictions, and is preferably zirconium oxide in the present invention; the lanthanum source can be a lanthanum source well known to those skilled in the art, without any special restrictions, and is preferably lanthanum oxide in the present invention; the molar ratio of the mixed lithium salt, zirconium source and lanthanum source is preferably x1:y1:z1; x1+z1=10, y1=z1-1, y is preferably 1~2.5, more preferably 1.5~2.5, and more preferably 2~2.5; the rotation speed of the first mixing is preferably 500~1000 rpm, more preferably 600~900 rpm, more preferably 700~900 rpm, and more preferably 800 rpm; the time of the first mixing is preferably 1~10 min, more preferably 3~8 min, more preferably 4~6 min, and most preferably 5 min.
[0050] Then, the carbon-doped lithium iron oxide material is added for a second mixing; the mass ratio of the total mass of the mixed lithium salt and the raw material of the surface coating layer except the lithium element to the carbon-doped lithium iron oxide material is preferably (1~10):(8~12); in some embodiments provided by the present invention, the mass ratio of the total mass of the mixed lithium salt and the raw material of the surface coating layer except the lithium element to the carbon-doped lithium iron oxide material is specifically 5:8, 7.5:12, 6.19:10 or 1:10; the rotation speed of the second mixing is preferably 2000~3000 rpm; in some embodiments provided by the present invention, the rotation speed of the second mixing is specifically 2000 rpm, 2500 rpm or 3000 rpm; the time of the second mixing is preferably 20~60 min, more preferably 30~60 min.
[0051] The third calcination is carried out in an oxygen-containing atmosphere, and the temperature is reduced to obtain a lithium ferrite lithium supplement; the oxygen-containing atmosphere can be an oxygen-containing atmosphere well known to those skilled in the art, and there is no special limitation. In the present invention, it is preferably compressed air; the temperature of the third calcination is preferably 500°C~700°C; in some embodiments provided by the present invention, the temperature of the third calcination is specifically 500°C, 600°C or 700°C; the time of the third calcination is preferably 6~15 h, more preferably 6~12 h; in some embodiments provided by the present invention, the time of the third calcination (i.e., the insulation time) is specifically 6 h, 8 h or 12 h; the heating rate of the third calcination is preferably 1~10°C / min, more preferably 2~8°C / min, more preferably 4~6°C / min, and most preferably 5°C / min; the cooling rate is preferably 20~40°C / min.
[0052] The present invention also provides a lithium ferrite lithium supplement prepared by the above preparation method.
[0053] The present invention also provides a lithium-ion battery, comprising the above-mentioned lithium ferrite lithium supplement.
[0054] More specifically, the lithium-ion battery includes a positive electrode; the positive electrode includes a positive electrode active layer; the positive electrode active layer includes a positive electrode active material, a lithium ferrite lithium supplement, a conductive agent and a binder; the positive electrode active material can be a positive electrode active material well known to those skilled in the art, without any special restrictions, and in the present invention, it is preferably one or more of lithium cobalt oxide, lithium manganese oxide, ternary nickel cobalt manganese lithium, lithium nickel manganese oxide, lithium iron phosphate and lithium manganese iron phosphate; the mass of the lithium ferrite lithium supplement is preferably 1% to 5% of the mass of the positive electrode active layer, and more preferably 3% to 5%; the mass of the conductive agent is preferably 1% to 5% of the mass of the positive electrode active layer, and more preferably 3% to 5%; the mass of the binder is preferably 1% to 5% of the mass of the positive electrode active layer, and more preferably 3% to 5%.
[0055] More specifically, the lithium-ion battery also includes a negative electrode; the negative electrode includes a negative electrode active material; the negative electrode active material is preferably one or more of artificial graphite, natural graphite, lithium titanate, metallic lithium, silicon-carbon composite material and silicon monoxide.
[0056] More specifically, the lithium-ion battery further comprises a diaphragm; the diaphragm is preferably a polypropylene, polyethylene diaphragm, or a polyethylene diaphragm coated with aluminum oxide on one side.
[0057] In order to further illustrate the present invention, a lithium ferrite lithium supplement agent, a preparation method thereof and an application thereof provided by the present invention are described in detail below in conjunction with examples.
[0058] The reagents used in the following examples are all commercially available.
[0059] Example 1
[0060] Preparation of Li5FeO4 / C: 10 g of glucose and 1 kg of iron oxide were uniformly mixed in 3 L of anhydrous ethanol, stirred at 500 rpm for 3 hours, and then the mixture was dried in a blast oven at 80 ° C for 12 h. After drying, the mixture was ground into fine powder, placed in an atmosphere furnace, heated to 300 ° C at a rate of 5 ° C / min under the protection of nitrogen, and kept at this temperature for 6 hours, thereby synthesizing carbon-supported iron oxide (Fe2O3 / C) material. After that, the synthesized Fe2O3 / C material was mixed with lithium oxide in a molar ratio of 1:5. The mixed powder was placed in a sagger and heated to 650 ° C at a rate of 5 ° C / min in the nitrogen environment of the atmosphere furnace again, and kept at this temperature for 24 hours, and finally prepared carbon-doped lithium iron oxide (Li5FeO4 / C) material.
[0061] LATP coating: 40 g of mixed lithium salt (mass ratio, lithium carbonate: lithium nitrate: lithium fluoride = 95:3:2), 20 g of alumina, 120 g of titanium oxide and 320 g of diammonium phosphate were mixed in a high-speed mixer at 800 rpm for 5 min. Then 800 g of Li5FeO4 / C was added for high-speed mixing, mixed at 3000 rpm for 30 min, placed in a box furnace, introduced with compressed air, and then heated to 500°C at a rate of 5°C / min, kept warm for 12 hours, and then cooled to room temperature at a rate of 20°C / min to obtain a lithium ferrite supplement.
[0062] Example 2
[0063] Preparation of Li5FeO4 / C: 50 g of polyvinyl pyrrolidone and 5 kg of iron oxide were uniformly mixed in 5 L of anhydrous ethanol, stirred at 200 rpm for 12 hours, and then the mixture was dried in a blast oven at 50 ° C for 24 h. After drying, the mixture was ground into fine powder, placed in an atmosphere furnace, and heated to 500 ° C at a rate of 5 ° C / min under the protection of nitrogen, and kept at this temperature for 3 hours, thereby synthesizing carbon-supported iron oxide (Fe2O3 / C) material. After that, the synthesized Fe2O3 / C material was mixed and ground with lithium oxide in a molar ratio of 1:6. The mixed powder was placed in a porcelain boat and heated to 850 ° C at a rate of 5 ° C / min in a nitrogen environment of an atmosphere furnace again, and kept at this temperature for 12 hours, and finally prepared carbon-doped lithium iron oxide (Li5FeO4 / C) material.
[0064] LATP coating: 60 g of mixed lithium salt (lithium hydroxide: lithium nitrate: lithium chloride = 80:15:5), 30 g of alumina, 180 g of titanium oxide and 480 g of diammonium phosphate were mixed in a high-speed mixer at 500 rpm for 10 min. Then 1200 g of Li5FeO4 / C was added for high-speed mixing, mixed at 2000 rpm for 60 min, placed in a box furnace, introduced with compressed air, and then heated to 700°C at a rate of 5°C / min, kept warm for 6 hours, and then cooled to room temperature at a rate of 40°C / min to obtain a lithium ferrite supplement.
[0065] Example 3
[0066] Li5FeO4 / C preparation: same as Example 1
[0067] LATP coating: 45 g of mixed lithium salt (lithium carbonate: lithium squarate: lithium fluoride = 90:12:8), 24 g of alumina, 150 g of titanium oxide and 400 g of diammonium phosphate were mixed in a high-speed mixer at 1000 rpm for 5 min. Then 1000 g of Li5FeO4 / C was added for high-speed mixing, mixed at 3000 rpm for 30 min, placed in a box furnace, introduced with compressed air, heated to 600°C at a rate of 5°C / min, kept warm for 8 hours, and then cooled to room temperature at a rate of 30°C / min to obtain a lithium ferrite supplement.
[0068] Comparative Example 1
[0069] The difference from Example 1 is:
[0070] The Li5FeO4 / C was replaced with regular Li5FeO4.
[0071] Preparation of Li5FeO4: Fe2O3 material and lithium oxide were mixed in a molar ratio of 1:5. The mixed powder was placed in a sagger and heated to 650°C at a rate of 5°C / min in a nitrogen environment of an atmosphere furnace again, and maintained at this temperature for 24 hours, finally preparing lithium iron oxide Li5FeO4 material.
[0072] LATP coating: 40 g of mixed lithium salt (mass ratio, lithium carbonate: lithium nitrate: lithium fluoride = 95:3:2), 20 g of alumina, 120 g of titanium oxide and 320 g of diammonium phosphate were mixed in a high-speed mixer at 800 rpm for 5 min. Then 800 g of Li5FeO4 was added for high-speed mixing, mixed at 3000 rpm for 30 min, placed in a box furnace, introduced with compressed air, heated to 500°C at a rate of 5°C / min, kept warm for 12 hours, and then cooled to room temperature at a rate of 20°C / min to obtain a lithium ferrite supplement.
[0073] Comparative Example 2
[0074] The difference from Example 1 is:
[0075] The mixed lithium salt in the LATP coating process is replaced with a single lithium salt.
[0076] Preparation of Li5FeO4 / C: 10 g of glucose and 1 kg of iron oxide were uniformly mixed in 3 L of anhydrous ethanol, stirred at 500 rpm for 3 hours, and then the mixture was dried in a blast oven at 80 ° C for 12 h. After drying, the mixture was ground into fine powder, placed in an atmosphere furnace, heated to 300 ° C at a rate of 5 ° C / min under the protection of nitrogen, and kept at this temperature for 6 hours, thereby synthesizing carbon-supported iron oxide (Fe2O3 / C) material. After that, the synthesized Fe2O3 / C material was mixed with lithium oxide in a molar ratio of 1:5. The mixed powder was placed in a sagger and heated to 650 ° C at a rate of 5 ° C / min in the nitrogen environment of the atmosphere furnace again, and kept at this temperature for 24 hours, and finally prepared carbon-doped lithium iron oxide (Li5FeO4 / C) material.
[0077] LATP coating: 40 g lithium carbonate, 20 g aluminum oxide, 120 g titanium oxide and 320 g diammonium phosphate were mixed in a high-speed mixer at 800 rpm for 5 min. Then 800 g Li5FeO4 / C was added for high-speed mixing. After mixing at 3000 rpm for 30 min, it was placed in a box furnace, and compressed air was introduced. It was heated to 500°C at a rate of 5°C / min and kept warm for 12 hours. Then it was cooled to room temperature at a rate of 20°C / min to obtain a lithium ferrite supplement.
[0078] Comparative Example 3
[0079] The difference from Example 1 is:
[0080] The cooling rate during the LATP coating process was adjusted to conventional natural cooling.
[0081] Preparation of Li5FeO4 / C: 10 g of glucose and 1 kg of iron oxide were uniformly mixed in 3 L of anhydrous ethanol, stirred at 500 rpm for 3 hours, and then the mixture was dried in a blast oven at 80 ° C for 12 h. After drying, the mixture was ground into fine powder, placed in an atmosphere furnace, heated to 300 ° C at a rate of 5 ° C / min under the protection of nitrogen, and kept at this temperature for 6 hours, thereby synthesizing carbon-supported iron oxide (Fe2O3 / C) material. After that, the synthesized Fe2O3 / C material was mixed with lithium oxide in a molar ratio of 1:5. The mixed powder was placed in a sagger and heated to 650 ° C at a rate of 5 ° C / min in the nitrogen environment of the atmosphere furnace again, and kept at this temperature for 24 hours, and finally prepared carbon-doped lithium iron oxide (Li5FeO4 / C) material.
[0082] LATP coating: 40 g of mixed lithium salt (mass ratio, lithium carbonate: lithium nitrate: lithium fluoride = 95:3:2), 20 g of alumina, 120 g of titanium oxide and 320 g of diammonium phosphate were mixed in a high-speed mixer at 800 rpm for 5 min. Then 800 g of Li5FeO4 / C was added for high-speed mixing, and after mixing at 3000 rpm for 30 min, it was placed in a box furnace, compressed air was introduced, and then heated to 500°C at a rate of 5°C / min and kept warm for 12 hours. Then the temperature was naturally cooled to room temperature to obtain a lithium ferrite lithium supplement.
[0083] Example 4
[0084] Preparation of Li5FeO4 / C: Same as Example 1.
[0085] LLZO coating: 24 g of mixed lithium salt (mass ratio, lithium carbonate: lithium nitrate: lithium fluoride = 95:3:2), 26 g of zirconium oxide and 50 g of lanthanum oxide were mixed in a high-speed mixer at 800 rpm for 5 min. Then 1000 g of Li5FeO4 / C was added for high-speed mixing, and mixed at 2500 rpm for 30 min. After that, it was placed in a box furnace, and compressed air was introduced. It was heated to 700°C at a rate of 5°C / min and kept warm for 12 hours. Then it was cooled to room temperature at a rate of 20°C / min.
[0086] Preparation of button cell: Add 0.85g of lithium iron phosphate as the positive electrode active material, 0.05g of lithium iron phosphate prepared in Examples 1 to 4 or Comparative Examples 1 to 3, 0.05g of lithium iron oxide supplement, 0.05g of conductive agent-Sp-Li, and 0.05g of binder-PVDF are uniformly mixed, and 3g of N-methylpyrrolidone is added to obtain a mixed slurry. Pour 4g of the mixed slurry on aluminum foil, use a 250μm scraper to evenly coat the slurry on the aluminum foil, and then place it in a 120℃ blast oven with a dew point of -60 to dry for 12 h, and then roll it to a compacted density of 2.8g / cm³. After punching, the positive electrode sheet is made; the metal lithium sheet is used as the negative electrode, the celgard2400 polypropylene porous membrane is used as the diaphragm, and the mixed solution of ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio is 1:1) of 1 mol / LLiPF6 is used as the electrolyte; the test battery is assembled in a glove box filled with argon gas.
[0087] The test battery was subjected to electrochemical performance test, and the first charge and discharge specific capacity, first charge and discharge efficiency and capacity retention rate were tested. The battery test was carried out at a constant temperature of 25°C, and the first charge and discharge mode was: 0.1C constant current charge, 0.1C constant current discharge. The subsequent long cycle mode was: 0.33C constant current charge, 0.33C constant current discharge. The cycle was 100 times.
[0088] The results are shown in Table 1.
[0089] Table 1 Electrochemical performance test results
[0090]
[0091] Under the same battery system, the first charge and discharge specific capacity, first charge and discharge efficiency and 100-cycle capacity retention rate of the battery prepared in Example 1-4 are better than those in Comparative Example 1-3, indicating that the lithium iron-rich lithium ion oxide of the composite solid electrolyte can effectively improve the lithium ion diffusion coefficient, reduce the internal delithiation energy barrier, reduce the consumption of lithium ions, and greatly improve the capacity retention rate of the battery.
[0092] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a lithium ferrite lithium supplement, characterized in that: The following steps are involved: S1) mixing an organic carbon source with iron oxide, and performing a first calcination in a protective atmosphere to obtain a carbon-supported iron oxide material; S2) mixing the carbon-supported iron oxide material with a lithium source, and performing a second calcination in a protective atmosphere to obtain a carbon-doped lithium iron oxide material; S3) The mixed lithium salt and the raw material of the surface coating layer except the lithium element are mixed for the first time, and then the carbon-doped lithium iron oxide material is added for a second mixing, and then calcined for a third time in an oxygen-containing atmosphere and cooled to obtain a lithium ferrite lithium supplement; the mixed lithium salt includes a first lithium salt, a second lithium salt and a third lithium salt; the melting point of the first lithium salt is greater than the melting point of the second lithium salt and the difference is greater than 100°C; the melting point of the third lithium salt is greater than the melting point of the first lithium salt and the difference is greater than 100°C; the surface coating layer is a solid electrolyte.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the first lithium salt, the second lithium salt and the third lithium salt is (80-95):(3-15):(2-5).
3. The preparation method according to claim 1, characterized in that: The organic carbon source is selected from one or more of glucose, polydopamine, resorcinol-formaldehyde resin, polyvinyl pyrrolidone, tannic acid, citric acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, anthracene, and aniline; The lithium source is selected from one or more of lithium oxide, lithium hydroxide, lithium oxalate and lithium carbonate; The first lithium salt is selected from lithium carbonate and / or lithium hydroxide; The second lithium salt is selected from one or more of lithium nitrate, lithium squarate, lithium acetate and lithium oxalate; The third lithium salt is selected from lithium fluoride and / or lithium chloride.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the organic carbon source to iron oxide is (0.01-0.05): (1-5); The molar ratio of iron oxide to lithium source in the carbon-supported iron oxide material is 1:(5-7).
5. The preparation method according to claim 1, characterized in that: The mixing in step S1) is carried out in an organic solvent, and after drying, the first calcination is carried out in a protective atmosphere; the ratio of iron oxide to organic solvent is (1~5) kg: (3~5) L; the mixing speed is 100~500 rpm; the mixing time is 3~12 h; The mixing in step S2) is performed by grinding; In the step S3), the rotation speed of the first mixing is 500-1000 rpm; the time of the first mixing is 1-10 min; the rotation speed of the second mixing is 2000-3000 rpm; the time of the second mixing is 20-60 min.
6. The preparation method according to claim 1, characterized in that: The temperature of the first calcination is 300°C to 500°C; the time of the first calcination is 3 to 6 hours; the heating rate of the first calcination is 1 to 10°C / min; The temperature of the second calcination is 650°C to 850°C; the time of the second calcination is 12 to 30 h; the heating rate of the second calcination is 1 to 10°C / min; The temperature of the third calcination is 500° C. to 700° C.; the time of the third calcination is 6 to 15 h; and the heating rate of the third calcination is 1 to 10° C. / min.
7. The preparation method according to claim 1, characterized in that: The cooling rate in step S3) is 20-40°C / min.
8. The preparation method according to claim 1, characterized in that: The surface coating layer is a lithium aluminum titanium phosphate solid electrolyte or a lithium lanthanum zirconium oxygen solid electrolyte; The mass ratio of the total mass of the mixed lithium salt and the raw materials of the surface coating layer except the lithium element to the carbon-doped lithium iron oxide material is (1-10): (8-12).
9. The lithium ferrite lithium supplement prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: A lithium ferrite supplement prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Method for preparing lithium iron phosphate-lithium vanadium phosphate by quenching method
CN102361080A
Inorganic-inorganic composite solid electrolyte ceramic membrane and preparation method thereof
CN108155412A
Lithium ion solid electrolyte and preparation method thereof
CN110212240A
Lithium supplement additive for lithium ion cathode material and preparation method thereof
CN112490415A
Solid electrolyte material and preparation thereof, lithium ion solid-state battery and application of lithium ion solid-state battery
CN115472902A
Cited By
Regeneration method and application of modified lithium ferrite treated by Lewis acid
CN120208300A
Gradient composite coated anode lithium supplement agent and preparation method and application thereof
CN121790560A
A gradient composite-coated positive electrode lithium supplementing agent, a preparation method and application thereof
CN121790560B
Battery diaphragm, lithium ion battery and preparation method of battery diaphragm
CN122456112A